Strengthening Institutional Policies as a Recovery Strategy for Bali Cultural Tourism and Sustainable Development - I Gusti Ayu Purnamawati (Global Review of Tourism and Social Sciences, 2025)
This study examines the institutional role of Paiketan Krama Istri, a women’s organization embedded in Balinese traditional villages, as a driving force for cultural tourism recovery and sustainable development in Buleleng Regency, Bali. Drawing on qualitative field research through literature studies, observations, and interviews, this research analyses how social capital embedded in Paiketan Krama Istri fosters solidarity, creativity, and innovation in post-pandemic tourism revitalization. Guided by feminist institutionalism and social capital theory, the study demonstrates that the organization’s emancipatory solidarity has strengthened local women’s participation in policy advocacy and tourism entrepreneurship. The findings reveal that Paiketan Krama Istri functions as an institutional bridge between local communities, traditional authorities, and government stakeholders, promoting inclusive and gender-responsive policy designs. The resulting policy model emphasizes collective empowerment, inter-institutional collaboration, and sustainable tourism recovery rooted in cultural values. This study contributes to the discourse on community-based tourism and gender equality by highlighting the transformative potential of women’s institutions in balancing cultural preservation, economic resilience, and social justice within one of the world’s most prominent cultural tourism destinations.